PENGARUH FISIOTERAPI DADA TERHADAP BERSIHAN JALAN NAFAS PADA ANAK BRONKOPNEUMONIA USIA 1-5 TAHUN DI RSUD TAMADA BONTANG - Achirulah Sari Dewi; Umi Kalsum; Nilam Noorma (Jurnal Cakrawala Ilmiah, 2024)
Bronchopneumonia is a global health problem that occurs in children. Children are an age group that is more susceptible to disease because their body organs are not yet functioning optimally. A common disease that often attacks children is bronchopneumonia.This research uses a quasi-experimental method with a pretest-posttest, one-group design approach. This design consists of one group, namely the intervention group, carried out by giving a pretest (assessing respiratory frequency and airway clearance), then giving chest physiotherapy and carrying out a post-test (assessing respiratory frequency and airway clearance), so as to allow researchers to test the benefits that occur after chest physiotherapy is given for respiratory frequency and airway clearance.The condition before chest physiotherapy showed that the effective cough decreased, the breathing pattern and breathing frequency worsened, the production of sputum, rales, wheezing, dyspnea, orthopnea, difficulty speaking, and restlessness increased, and the RR increased. After chest physiotherapy, it showed that effective coughing increased, breathing patterns and breathing frequency improved, sputum production, rhonchi, wheezing, dyspnea, orthopnea, difficulty speaking, and restlessness decreased, and RR decreased.Based on the results of the Paired-T Test, the significance value of the p-Value is 0.001 (<0.05), indicating that there is an influence of chest physiotherapy on the patient's airway clearance.